Reclaiming gender : transsexual grammars at the Fin de Siecle - More, Kate (ed.); Whittle , Stephen (ed.) (London, 1999)
An interdisciplinary work bringing together an international group of transgender writers, this text provides a collection of essays that are central to both academia and activism. Based on academic and "street" experiences, the book addresses the practical issues faced in changing the world view of gender while forcing theory a step forward from limitations of "queer", feminism and postmodernism. In a wide-ranging set of contributions, it addresses our engendered places now and what we can aim for in the future. It evaluates the mechanism we can use to galvanize both the micro theories of gender as a personal experience of oppression and the macro theories of gender as a site of social regulation. The collection aimes to take identity politics and reclaim identity for the "self".
Keywords: Transsexualism